A Universal Cosolvent Evaporation Strategy Enables Direct Printing of Perovskite Single Crystals for Optoelectronic Device Applications. Issue 9 (24th January 2022) - Corzo, Daniel; Wang, Tonghui; Gedda, Murali; Yengel, Emre; Khan, Jafar I; Li, Ruipeng; Niazi, Muhammad Rizwan; Huang, Zhengjie; Kim, Taesoo; Baran, Derya; Sun, Dali; Laquai, Frédéric; et al.
Abstract: Solution‐processed metal halide perovskite (MHP) single crystals (SCs) are in high demand for a growing number of printed electronic applications due to their superior optoelectronic properties compared to polycrystalline thin films. There is an urgent need to make SC fabrication facile, scalable, and compatible with the printed electronic manufacturing infrastructure. Here, a universal cosolvent evaporation (CSE) strategy is presented by which perovskite SCs and arrays are produced directly on substrates via printing and coating methods within minutes at room temperature from drying droplets. The CSE strategy successfully guides the supersaturation via controlled drying of droplets to suppress all crystallization pathways but one, and is shown to produce SCs of a wide variety of 3D, 2D, and mixed‐cation/halide perovskites with consistency. This approach works with commonly used precursors and solvents, making it universal. Importantly, the SC consumes the precursor in the droplet, which enables the large‐scale fabrication of SC arrays with minimal residue. Direct on‐chip fabrication of 3D and 2D perovskite photodetector devices with outstanding performance is demonstrated. The approach shows that any MHP SC can now be manufactured on substrates using precision printing and scalable, high‐throughput coating methods. Abstract : Perovskite single crystals (SCs) are grown on‐demand at room temperature and integrated directly onto optoelectronic devices via printing and coating using a scalable cosolvent evaporation (CSE) strategy. The CSE strategy controls supersaturation and suppresses competing nucleation during drying to yield high‐quality SCs of 2D, 3D, lead‐free, and mixed‐ion perovskites with minimal residue.